1983
DOI: 10.1002/bjs.1800700514
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernias: When do they occur?

Abstract: Incisional herniation remains a major problem for the general surgeon. Most published studies have followed up patients for 6-12 months after operation. In this study, 363 patients, known not to have an incisional hernia at 1 year, were reviewed between 2.5 and 5.5 years after operation. Twenty-one patients (5.8 per cent) were found to have developed incisional hernias. None of the causal factors previously implicated in the aetiology of incisional herniation (wound infection, male sex, obesity, age, postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(72 citation statements)
references
References 4 publications
2
66
1
3
Order By: Relevance
“…The short follow up period (6 months) may be a possible reason for the absence of incisional hernias in this study since > 5% of incisional hernias have been reported to occur after 6-12 months [16].…”
Section: Discussionmentioning
confidence: 86%
“…The short follow up period (6 months) may be a possible reason for the absence of incisional hernias in this study since > 5% of incisional hernias have been reported to occur after 6-12 months [16].…”
Section: Discussionmentioning
confidence: 86%
“…Ellis, Gajraj and George 13 obtained an incidence of 64.6% female population in their study of 383 patients. Goel and Dubey 43 series have male to female ratio 1:1.25 ratio.…”
Section: Discussion:-mentioning
confidence: 97%
“…Laparotomi kesileri aralıklı ya da devamı sütür tekniğiyle, emilebilen veya emilmeyen sütürlerle, tabakalı ya da tek kat şeklinde kapatılabilmekte, ancak bunlardan hiçbirisinin İH gelişme sıklığına katkısını açıklamak tam olarak mümkün olmamaktadır. 11,25,[28][29][30][31][32] Günümüzde önerilen yöntem; az doku reaksiyonuna neden olan, enfeksiyona dirençli, emilebilen monofilaman yapıda sütür materyali kullanılarak, devamlı sütür tekniği ile yapılan karın kapatılması tekniğidir. 11,25,28,29,32 Literatürde karın kapatılması tekniğiyle ilgili önemli faktörlerden biri olarak insizyon uzunluğunun en az dört katı uzunluğunda sütür materyali kullanmanın gerekliliği de vurgulanmaktadır.…”
Section: Discussionunclassified